Conflict Resolution in the Interactionism Symbolyc Prespective - Sidik Puryanto (Mahesa Research Center, 2023)
This study describes conflict resolution using the theory of symbolic interactionism by Herbert Blumer and George Herbert Mead. The theory of symbolic interactionism contains three main substances, namely mind, self and society. The self-concept put forward has three criteris, namely emotions, attitudes, beliefs, and values. Self-concept is an attempt to understand and interpret the actions of others through symbols, so that an agreement or compromise occurs. Conflict resolution is an effort to understand and interpret actions based on the symbols of conflict actors, so that an agreement can be reached, thereby creating conflict resolution.The discussion of conflict resolution uses the theory of symbolic interactionism by Herbert Blumer and George Herbert Mead, that self and self-concept are conflict resolution construction models that prioritize discussion and negotiation.